Analisis Return Saham Perusahaan Nasional dan Korporasi Multinasional di Bursa Efek Indonesia: Studi Kasus Perusahaan Manufaktur Tahun 2022 - Putra, Putu Adi; Fikri, Muhammad Ali; Astuti, Widia (Jurnal Riset Mahasiswa Akuntansi, 2024)
This research aims to analyze stock returns in National Companies and Multinational Corporations on the Indonesian Stock Exchange. The research examines the influence of current ratio, debt to total assets, return on assets on stock returns of national and multinational companies. The research population used manufacturing companies listed on the IDX in 2022. Based on the results of regression testing using a sample of 113 national manufacturing companies, it was found that the financial ratios CR and DAR each had no effect on returns, while the financial ratio ROA had an effect on returns for the sample of 32 multinational manufacturing companies DAR ratio has a positive influence on stock returns. This research provides evidence that there is an influence of ratios on stock returns of national manufacturing companies and multinational corporations.